MOEA/PC: multiobjective evolutionary algorithm based on polar coordinates - Denysiuk, Roman (2015)
Author proof. Proceedings of 8th International Conference Evolutionary Multi-Criterion Optimization (EMO 2015), part I. LNCS, vol. 9018, 2015.